A Double Self‐Assembly Process for Versatile Reduced‐Graphene‐Oxide Layer Deposition and Conformal Coating on 3D Structures. Issue 23 (5th October 2017) - Jia, Guobin; Plentz, Jonathan; Presselt, Martin; Dellith, Jan; Dellith, Andrea; Patze, Sophie; Tölle, Folke Johannes; Mülhaupt, Rolf; Andrä, Gudrun; Falk, Fritz; Dietzek, Benjamin
Abstract: In this work, a double self‐assembly (DSA) process is demonstrated based on the surface interaction between graphene flakes (GFs) and surfactant molecules at water/air interface, leading to the formation of a stable and dense monolayer of graphene flakes (MGFs) floating on water surface. The thus prepared MGFs can be easily transferred onto various substrates almost independent of their surface wettability. During deposition both the GFs and excess surfactant molecules rearrange themselves in a self‐assembled way, so that optimal compression of the MGFs is ensured. Consequently, high performance deposition of MGFs can be easily achieved. The here‐reported process combines a fast, reliable, equipment‐free large‐area (>75 cm 2 in this work) high performance MGFs deposition onto most substrates irrespective to their wettability. Moreover, the DSA process enables an excellent conformal coating of MGFs on 3D structures. Thus, this technology has the potential to pave the way to many large‐scale affordable applications of low‐cost graphene feedstocks. Abstract : A double self‐assembly process is disclosed based on surface interaction between graphene flakes and surfactant molecules at water/air interface. It enables formation of high‐performance monolayer of graphene flakes and allows a fast, reliable, and equipment‐free transferring of the formed monolayer on various substrates almost independent of their surface wettability. A conformal coating on complex 3D structures can be achieved.